Anti-Mullerian Hormone Assessment in Assisted Reproductive Technique Outcome and Natural Conception - Sellami, Inès; Barbotin, Anne Laure; Bernard, Valérie; Robin, Geoffroy; Catteau-Jonard, Sophie; Sonigo, Charlotte; Peigné, Maeliss (Seminars in Reproductive Medicine, 2024)
In recent years, the prevalence of infertility has increased, and appears to affect approximately one in six couples. Some of them must perform assisted reproductive techniques (ART) in order to achieve pregnancy. As a result, growing interest has arisen about predictive factors of pregnancy and live birth with and without ART. Anti-Mullerian hormone (AMH) is a glycoprotein discovered in the 1950s in male embryonic sexual differentiation. Later, in 1984, its role in folliculogenesis was reported: secreted by granulosa cells, this hormone is involved in the regulation of the recruitment of primordial follicles and in follicular growth. AMH assays were developed for women in 1990s, and the serum AMH level has rapidly become a crucial element in managing women's fertility. Based mainly on its ability to be a quantitative but indirect marker of ovarian reserve, the serum AMH assay is widely used in reproductive medicine and ART. This review summarizes current knowledge of the AMH assessment in the field of reproductive medicine. We focus on the role of AMH level to predict spontaneous pregnancy occurrence, ART outcomes, and fertility preservation outcomes.
Keywords: AMH; fertility; reproductive medicine; pregnancy; ART